ISLAMIC ECONOMIC THOUGHT OF MUHAMMAD ABDUL MANNAN - Al Fachrodzi, Azriel; Kurniawan, Rachmad Risqy; Umar Riaz, Muhammad (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. Muhammad Abdul Mannan is one of the contemporary economic figures who exist today, he belongs to the mainstream. According to M. Mannan, what distinguishes Islamic economics from other modern economic systems, according that, in the Islamic framework, economic prosperity and welfare are means to achieve spiritual and moral goals, and economic prosperity is a means to achieve spiritual goals and moral goals. Research Purpose. To describe the Islamic Economic Thought of Muhammad Abdul Mannan. Research Method. Gather some literature in books, the internet, and journals on the same topic and make an analysis based on context. Literature that has been used for 5 years ago. Findings. Muhammad Abdul Mannan's thoughts on the Islamic paradigm, distribution in Islam, and consumption from an Islamic economic point of view. Muhammad A. Mannan considers the concept of development in Islam to have advantages over modern development concepts. In the context of economic development planning, fiscal policy design refers to policies made by the government to direct a country's economy through government spending and revenue (in the form of taxes). Conclusion. M. Mannan proposes modifications to conventional Neo-Classical economic theory and its tools to bring about changes in value orientation, institutional arrangements, and achievable goals.